2013
DOI: 10.1093/cercor/bht121
|View full text |Cite
|
Sign up to set email alerts
|

Neuromagnetic Evidence of Abnormal Movement-Related Beta Desynchronization in Parkinson's Disease

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder associated with debilitating motor, posture, and gait abnormalities. Human studies recording local field potentials within the subthalamic nucleus and scalp-based electroencephalography have shown pathological beta synchronization throughout the cortical–basal ganglia motor network in PD. Suppression of such pathological beta synchronization has been associated with improved motor function, which may explain the effectiveness of deep-brain stimulation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
156
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 138 publications
(169 citation statements)
references
References 64 publications
10
156
3
Order By: Relevance
“…Previous studies investigating task-induced modulations of alpha-and beta-band power have not identified the dissociation shown in this study (Pfurtscheller and Lopes da Silva, 1999;de Lange et al, 2008;Bauer et al, 2012;ter Horst et al, 2013;Heinrichs-Graham et al, 2014). However, those studies did not investigate differential effects of task demand on spectral profiles nor included a neutral control condition.…”
Section: Discussioncontrasting
confidence: 57%
“…Previous studies investigating task-induced modulations of alpha-and beta-band power have not identified the dissociation shown in this study (Pfurtscheller and Lopes da Silva, 1999;de Lange et al, 2008;Bauer et al, 2012;ter Horst et al, 2013;Heinrichs-Graham et al, 2014). However, those studies did not investigate differential effects of task demand on spectral profiles nor included a neutral control condition.…”
Section: Discussioncontrasting
confidence: 57%
“…In addition to excess b, PD patients were found to have diminished g response amplitude and peak frequency. 78 Taken together, these data fit into the model proposed by Shimamoto and colleagues in which excess motor cortical b synchrony, manifesting clinically as hypokinesia, is a result of strong pathological b oscillations passed from the basal ganglia. 177 This increased cortical b synchronization, in turn, leads to reinforcement of the basal ganglia b oscillations through pathological M1 b-phase g-amplitude coupling (Fig.…”
Section: Mechanistic Understandingsupporting
confidence: 75%
“…Briefly, there is an event-related desynchronization (ERD) in the beta-frequency range (14–28 Hz) that peaks before movement onset and continues slightly after movement execution, which is termed the pre-movement beta ERD response. There is an event-related synchronization (ERS) in the gamma-frequency range that coincides with the onset of movement and is relatively brief (i.e., ~200 ms), and finally there is a post-movement beta ERS that reaches maximum amplitude slightly after the termination of movement (Cheyne et al, 2008; Gaetz et al, 2010, 2011; Hall et al, 2011; Heinrichs-Graham et al, in press; Jurkiewicz et al, 2006; Tzagarakis et al, 2010; Wilson et al, 2010, 2011). This latter response is generally termed the post-movement beta rebound (PMBR).…”
Section: Introductionmentioning
confidence: 99%